Exploring the gap between research and practice in human resource management (HRM): a scoping review and agenda for future research - Philip Negt; Axel Haunschild (Management Review Quarterly, 2024)
The call for evidence-based decisions in HR has become a heated debate in recent years. An alleged research-practice gap has been identified by a number of HRM scholars, leading to recommendations for practice. To what extent the assumption of this gap is justified, theoretically or empirically, remains vague, however. Thus, building on a systematic literature search and the formulation of eligibility criteria for articles, we conducted a scoping review of the current research landscape. Our aim was to explore the constituent components, causes and consequences of the gap. Overall, it was found that research activity has so far been heterogeneous, a significant number of articles were conceptually driven, and a large proportion related to knowledge deficits of HR practitioners. A subset of consistent survey-based studies indicated little awareness of empirically supported practices in personnel selection. The qualitative, mixed-method, and content-analysis studies revealed other influences, such as research with limited practical relevance or divergent interests between scholars and practitioners (e.g., employee motivation). Based on the conceptual contributions, three thematic clusters were identified as causes for the gap: (1) communication barriers (e.g., insufficient interfaces), (2) methodological issues (e.g., rigor-relevance tensions), (3) accessibility, visibility, and dissemination of HR research (e.g., oversimplification of practical implications). There was a strong emphasis on presumed causes and their resolution, with less consideration given to the expected consequences of the gap (e.g., poorer organizational outcomes). Despite preliminary empirical indications for the existence of a research-practice gap in particular areas of HRM, many articles tend to focus on overarching recommendations for practice. We conclude that the HRM research-practice gap in itself has not yet been sufficiently empirically investigated. In view of this, we discuss implications and develop an agenda for future research.
Keywords: B4; M5; 650; HRM; Research-practice gap; Knowing-doing; Rigor-relevance; Scholar-practice divide